PEMODELAN INVERSI 2-D MENGGUNAKAN DATA MAGNETOTELLURIK DAERAH PANAS BUMI WAY SELABUNG, KABUPATEN OGAN KOMERING ULU SELATAN, PROVINSI SUMATERA SELATAN: 2-D INVERSION MODELING USING MAGNETOTELLURIC DATA AT WAY SELABUNG GEOTHERMAL AREA, SOUTH OGAN KOMERING ULU REGENCY, SOUTH SUMATERA PROVINCE - ilmi, irpan; Syafri, Ildrem; Haryanto, Agus Didit; Zarkasyi, Ahmad (Buletin Sumber Daya Geologi, 2020)
One of the physical properties of rocks that can be used to analyze a geothermal system is the resistivity of rock. Magnetotelluric method is one method that can be used to determine the resistivity of rock. MT measurements are carried out at 30 measuring points with north-south directed paths and the distance between measuring points is around 2000 meters. This research aims to do 2-D inversion modeling in determining location, delineation, and depth of the geothermal potential of Way Selabung. Based on the results of MT data analysis and 2-D inversion modeling, the Way Selabung geothermal system is in the graben structure zone. The manifestation of Way Selabung, Lubuk Suban and Selabung Damping hot water manifestations is formed due to intersection of Way Selabung, Kotadalam and Akarjangkang faults in a hydrogeological pattern in the outflow zone. 2-D modeling results show the top there is a group of low resistivity value <10 Ohm.m with a thickness of about 1500 meters from the surface which is interpreted as caprock. At the bottom there is a group of resistivity values of around 30-100 Ohm.m with a depth of 1500 meters to 1750 meters which is interpreted as a reservoir zone.